Dynamics of Social Conflict in Hindu and Samawa Ethnic Communities from the Perspective of Sociology Education - Esa El Hawa; Bunyamin Maftuh; Wilodati, Wilodati (Yayasan Insan Mulia Bima, 2024)
The multicultural society is composed of diversity and various cultures that involve values, cultures, and customs emphasized on mutual acceptance of each other in society's life. The conflict that occurred in 2013 involving the Balinese (Hindu) ethnic group and the indigenous population of Sumbawa, this conflict in Sumbawa is the result of a series of conflict events in 1980, 2003, and then occurred again in 2013. This research aims to understand the dynamics of social conflicts between Hindu and Samawa ethnic communities from the perspective of sociology education. The method used is through library research. The results of the study show that from the perspective of sociology education, this ethnic conflict can be a relevant learning material to understand the social construction of multiethnic societies